2021
DOI: 10.3389/fphy.2021.706056
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of a Magnetic Cloud From Solar Orbiter and Wind Spacecraft In-situ Measurements

Abstract: Coronal mass ejections (CMEs) represent one type of the major eruption from the Sun. Their interplanetary counterparts, the interplanetary CMEs (ICMEs), are the direct manifestations of these structures when they propagate into the heliosphere and encounter one or more observing spacecraft. The ICMEs generally exhibit a set of distinctive signatures from the in-situ spacecraft measurements. A particular subset of ICMEs, the so-called Magnetic Clouds (MCs), is more uniquely defined and has been studied for deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The minimum reduced χ 2 value is 1.44, and the corresponding Q = 0.00687. The set of main parameters as presented in Table 1 represents the optimal output from the fitting procedure with uncertainty estimates based on 90% confidence limits (Press et al 2007;Hu et al 2021b). The parameter C has a magnitude close to 1, indicating significant deviation from a cylindrically symmetric configuration, as we will demonstrate below.…”
Section: A Quasi-3d MC Model: Freidberg Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum reduced χ 2 value is 1.44, and the corresponding Q = 0.00687. The set of main parameters as presented in Table 1 represents the optimal output from the fitting procedure with uncertainty estimates based on 90% confidence limits (Press et al 2007;Hu et al 2021b). The parameter C has a magnitude close to 1, indicating significant deviation from a cylindrically symmetric configuration, as we will demonstrate below.…”
Section: A Quasi-3d MC Model: Freidberg Solutionmentioning
confidence: 99%
“…Such occasions are generally rare and such a validation approach has been carried out for the 2D GS reconstructions of a handful of MC events (Hu et al 2005;Möstl et al 2008Möstl et al , 2009. The latest applications to the quasi-3D model outputs have been performed as well (Hu et al 2021b;Hu 2021). For example, in Hu et al (2021b) an MC structure was observed by both the Solar Orbiter (SO) at a heliocentric distance of ∼0.8 au and the Wind spacecraft at Earth with a longitudinal separation angle of ∼4°.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such occasions are generally rare and such a validation approach has been carried out for the 2D GS reconstructions of a handful of MC events (Hu et al 2005;Möstl et al 2008Möstl et al , 2009. The latest applications to the quasi-3D model outputs were performed as well (Hu 2021;Hu et al 2021b). For example, in Hu et al (2021b), an MC structure was observed by both the Solar Orbiter (SO) at a heliocentric distance ∼0.8 au and Wind spacecraft at Earth with a longitudinal separation angle ∼ 4 • .…”
Section: Introductionmentioning
confidence: 99%
“…The latest applications to the quasi-3D model outputs were performed as well (Hu 2021;Hu et al 2021b). For example, in Hu et al (2021b), an MC structure was observed by both the Solar Orbiter (SO) at a heliocentric distance ∼0.8 au and Wind spacecraft at Earth with a longitudinal separation angle ∼ 4 • . The analyses of the MC structure with both the 2D GS reconstruction and the quasi-3D model fitting were carried out by using the Wind spacecraft measurements and the expected values of magnetic field along the SO spacecraft path were produced for both models.…”
Section: Introductionmentioning
confidence: 99%